Temperature compensated crystal oscillator design in Keysight ADS - A. N. Lyashuk; A. V. Kosykh (Омский научный вестник)
The article proposes an all-embracing approach to designing a temperature compensated crystal oscillator in Keysight ADS CAD system, which allows: to investigate the conditions for the occurrence of self-oscillations in a given oscillator circuit; analyze the temperature-frequency characteristics of the resonator; form requirements for the frequency control function; simulate noise characteristics of the generator; optimize the circuit according to the given parameters. In contrast to the well-known numerical design of a thermally compensated crystal oscillator in SPICE programs with subsequent analysis of the results in a mathematical program, for example, Mathcad, the proposed method allows us to investigate the real shape of oscillations, the spectral purity of the output signal, take into account the nonlinear influence of the circuit and more subtle effects.